5
$\begingroup$

The Arithmetic Mean (A.M) between two numbers exceeds their Geometric Mean (G.M.) by $2$ and the GM exceeds the Harmonic Mean (H.M) by $1.6$. Find the numbers.

My Attempt: Let the numbers be $a$ and $b$. Then, $$A.M=\dfrac {a+b}{2}$$ $$G.M=\sqrt {ab}$$ $$H.M=\dfrac {2ab}{a+b}$$ According to question: $$\dfrac {a+b}{2} =\sqrt {ab}+2$$ $$\dfrac {a+b}{2}-2=\sqrt {ab}$$ $$a+b-4=2\sqrt {ab}$$ Also, $$\sqrt {ab}=\dfrac {2ab}{a+b} + 1.6$$ Then, $$a+b-4=2(\dfrac {2ab}{a+b} + 1.6)$$ $$a+b-4=\dfrac {4ab+3.2(a+b)}{a+b}$$ $$(a+b-4)(a+b)=4ab+3.2(a+b)$$ $$(a+b)^2-4(a+b)=4ab+3.2a+3.2b$$

How do I solve further?

$\endgroup$
13
$\begingroup$

$$AM=GM+2$$

$$GM=HM+1.6$$

Since $$GM^2=AM\cdot HM,$$

$$GM^2=(GM+2)(GM-1.6)$$

$$GM^2=GM^2+0.4GM-3.2$$

$$GM=8$$

$$AM=10$$

$$\sqrt{ab}=8, \frac{a+b}{2}=10$$

$$ab=64, a+b = 20$$

The numbers are $16$ and $4$.

$\endgroup$
2
  • $\begingroup$ For question about plotting, perhaps stackoverflow is more appropriate? here is a possible lead, try function histfit in Matlab? $\endgroup$ – Siong Thye Goh Apr 30 '18 at 16:45
  • $\begingroup$ mathworks.com/help/stats/histfit.html i think android can access that, it is just a regular website. $\endgroup$ – Siong Thye Goh Apr 30 '18 at 17:16
2
$\begingroup$

I don't know why I do this, but here is the general case.

Suppose $am = gm+u$ and $gm = hm+v$ with $u, v \ne 0$ and $u \ne v$.

Since $hm \le gm \le am $, $u \ge 0$ and $v \ge 0$.

Since $gm^2 = am\cdot hm$, $gm^2 =(gm+u)(gm-v) =gm^2+gm(u-v)-uv $ so $gm(u-v) =uv$. Therefore $u > v$ and $gm =\dfrac{uv}{u-v} $.

Then $am =gm+u =\dfrac{uv}{u-v}+u =\dfrac{uv+u(u-v)}{u-v}+u =\dfrac{u^2}{u-v} $ and $hm =gm-v =\dfrac{uv}{u-v}-v =\dfrac{uv-v(u-v)}{u-v} =\dfrac{v^2}{u-v} $.

If there are only two values, $a$ and $b$, then $\dfrac{a+b}{2} =\dfrac{u^2}{u-v} $ and $\sqrt{ab} =\dfrac{uv}{u-v} $ so $b =\dfrac{u^2v^2}{a(u-v)^2} $ and $\dfrac{u^2}{u-v} =\dfrac{a+\dfrac{u^2v^2}{a(u-v)^2}}{2} =\dfrac{a^2(u-v)^2+u^2v^2}{2a(u-v)^2} $ or $2au^2(u-v) =a^2(u-v)^2+u^2v^2 $.

Solving $a^2(u-v)^2-2u^2(u-v)a+u^2v^2 =0$,

$\begin{array}\\ a &=\dfrac{2u^2(u-v)\pm\sqrt{4u^4(u-v)^2-4(u-v)^2u^2v^2}}{2(u-v)^2}\\ &=\dfrac{u^2(u-v)\pm u(u-v)\sqrt{u^2-v^2}}{(u-v)^2}\\ &=\dfrac{u^2\pm u\sqrt{u^2-v^2}}{u-v}\\ &=u\dfrac{u\pm \sqrt{u^2-v^2}}{u-v}\\ \text{and}\\ b &=\dfrac{2u^2}{u-v}-a\\ &=\dfrac{2u^2}{u-v}-\dfrac{u^2\pm u\sqrt{u^2-v^2}}{u-v}\\ &=\dfrac{2u^2-u^2\mp u\sqrt{u^2-v^2}}{u-v}\\ &=\dfrac{u^2\mp u\sqrt{u^2-v^2}}{u-v}\\ \end{array} $

For this case, $u=2$ and $v=1.6$.

$gm =\dfrac{2\cdot 1.6}{2-1.6} =\dfrac{3.2}{.4} =8 $.

To get $a$ and $b$, $\sqrt{u^2-v^2} =\sqrt{4-2.56} =\sqrt{1.44} =1.2 $ so $a =2\dfrac{2\pm 1.2}{.4} =2\dfrac{3.2, .8}{.4} =2(8, 2) =(16, 4) $ and $b =(4, 16) $.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.